SATISFACTION OF CONSUMERS OF BOUQUET PRODUCTS IN PONOROGO, EAST JAVA - Paundra Fatikah Prabandari; Wijianto Wijianto; Fery Setiawan (Journal of Management Small and Medium Enterprises (SMEs), 2025)
This study aims to determine consumer satisfaction with bouquet products in Ponorogo among Jenar Buket Ponorogo customers. This study employs a quantitative approach with the accidental sampling method of 100 consumers. The data analysis techniques used were the validity test, reliability test, normality test, heteroscedasticity test, multicollinearity test, autocorrelation test, multiple linear regression test, determination test, and hypothesis test, which were processed using the Statistical Package for the Social Sciences (SPSS) for Windows, version 25. The results of this study indicate that product quality and product customization have a positive and significant effect on consumer satisfaction of Jenar Buket, while service performance does not have a significant effect. The results of the determination test indicated that product quality, service performance, and product customization had an influence of 67.5% on consumer satisfaction, while the remaining 33% was influenced by other variables not explained in this study. Keywords: Quality Product; Performance Service; Customization Product